Chemical composition of essential oil for Thymus population from Albania - Jonida Salihila; Dorina Shengjergji; Dhimiter Peci; Aida Dervishi (Zaštita Materijala)
This study presents data about chemical composition of essential oils for Thymus populations from the Albania. The genus Thymus contains about 350 species of aromatic plants in the family Lamiaceae. It is in the form of a beautiful shrub with numerous branches used often as decorative plant besides it uses for culinary and medical purposes. Thymus plants are part of spontaneous flora in Albania and almost throughout the Mediterranean areas. Thymus vulgaris, Thymus capitatus and Thymus serpyllum samples from different areas of Albania were taken in July 2017. The air dried plant samples were cut in small pieces (1-2 cm) and after that were subjected to European Pharmacopoeia apparatus (Clevenger type) for 4 hours to obtain Thymus essential oil. The chemical composition of essential oils was analyzed using GC/FID technique. The oil of each Thymus samples was injected in a Varian 450 GC. VF-1ms capillary column (30 m x 0.33 mm x 0.25 um) were used for separation of compounds. 40-65 compounds were found in analyzed samples. Para-Cymene, gama-Terpinen, Thymol and Carvacrol were identified as main constituents and all analyzed essential oils of Thymus samples from Albania. Para-Cymene was the main constituent for Thymus vulgaris samples. Carvacrol was found in higher percentage for Thymus capitatus and Thymus serpyllum. Thymol was in higher percentage for Thymus vulgaris and Thymus serpyllum. Total of Thymol and Carvacrol were higher for Thymus serpyllum samples. The same compounds were found for all Thymus samples but were noted differences in percentage between them. This is related with differences between species obtained for analysis but is not excluded the impact of geographic and geological factors. Data reported in this paper were similar to those published in previous works in Balkan and Mediterranean area.